Partisipasi Masyarakat dalam Pengelolaan Badan Usaha Milik Desa Makmur Sejahtera - Karmila Karmila; Eka Yulyana; Evi Priyanti (Universitas Musamus, Merauke, Papua, 2022)
Village-Owned Enterprises (BUMDes) are seen as entities that enable communities to achieve economic independence. One strategy to ensure that BUMDes operate properly is to include the local community. Until far, the community's involvement to BUMDes Makmur Sejahtera in Lemahmulya Village, Majalaya District, Karawang Regency has been negligible, both in planning and execution. The goal of this research is to ascertain the degree to which the community participates in BUMDes management. The qualitative descriptive approach was used in this investigation, and the following findings were obtained: 1) Community participation in BUMDes planning decision-making is still suboptimal, as indicated by the involvement of just a few groups. 2) Effective village community participation in the execution of the BUMDes program is shown by the community's active participation in the program's implementation. 3) The village community's participation in achieving the advantages of BUMDes is highly positive, as it enables small business operators to establish or expand their enterprises. 4) Community participation in suggesting activities for the BUMDes program is still suboptimal since the community lacks any methods of providing feedback and evaluation on the program's operation.